Suitability of Mobile Banking Interfaces for the Elderly Users: A Literature Review - Wilundah, Kisiali Daniel (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
This literature review evaluates the suitability of mobile banking interfaces for elderly users, a demographic that is increasingly engaged with digital platforms yet often encounters usability challenges. Given the critical role of mobile banking as a financial service, it is essential to understand how interface design impacts elderly users to ensure inclusive access. This review synthesizes findings from existing research on the unique needs and preferences of elderly users, identifying key factors that influence their interaction with mobile banking platforms. Support features of mobile phones, such as adjustable text sizes, voice commands, and touch sensitivity adjustments, are examined for their impact on usability for the elderly. The study design involves a comprehensive literature review, systematically analyzing articles from academic databases and industry reports published between 2019 and 2024. Sampling techniques include keyword searches and selection based on relevance and quality, focusing on studies addressing usability challenges and design solutions for elderly users. Key study tools utilized in this review include usability assessment frameworks and design guidelines tailored to the elderly. The review highlights that elderly users often face difficulties with small text sizes, complex navigation, and insufficient feedback mechanisms. Effective strategies identified include larger touch targets, simplified interfaces, and enhanced customer support, which significantly improve usability for this group. However, gaps remain in understanding how to integrate accessibility features without compromising user experience. This review underscores the importance of user-centered design principles tailored to the elderly, advocating for the incorporation of intuitive design and accessibility features in mobile banking interfaces. Financial institutions can better serve the aging population by addressing these challenges, thereby enhancing overall user experience and promoting digital inclusivity.